1988
DOI: 10.1093/bja/60.5.582
|View full text |Cite
|
Sign up to set email alerts
|

Use of Diltiazem to Control Circulatory Fluctuations During Resection of a Phaeochromocytoma

Abstract: This report describes the use of diltiazem to control circulatory fluctuations during anaesthesia in five patients undergoing resection of a phaeochromocytoma. Diltiazem was administered continuously i.v. before anaesthesia and during surgery until the draining vein from the tumour had been ligated. Arterial pressure and systemic vascular resistance decreased in association with the infusion of diltiazem. Heart rate was stable, and there was no ventricular tachyarrhythmia. Arterial pressure was controlled easi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…[98] Unlike phenoxybenzamine, calcium channel blockers will not cause dangerous hypotension and are relatively short acting. It is especially useful for normotensive patients or those with very mild hypertension.…”
Section: Pharmacological Treatment Of Pheochromocytomamentioning
confidence: 99%
“…[98] Unlike phenoxybenzamine, calcium channel blockers will not cause dangerous hypotension and are relatively short acting. It is especially useful for normotensive patients or those with very mild hypertension.…”
Section: Pharmacological Treatment Of Pheochromocytomamentioning
confidence: 99%
“…[12] reported haemodynamic stability in the management of a case of phaeochromocytoma using a midazolam‐sufentanil anaesthetic. Other authors have suggested that calcium channel blockers and magnesium infusions may be able to interfere with the synthesis and release of catecholamines during tumour manipulation [13, 14]. However, hypotension may be protracted after tumour removal with the use of such agents.…”
Section: Discussionmentioning
confidence: 99%
“…As described by Dr. Emmanuel Bravo (Cleveland Clinic, Cleveland, Ohio), calcium channel blockers (the dihydropyridines) may also be suitable for control of blood pressure and symptoms in patients with pheochromocytoma 29–34 . Because these drugs do not cause orthostatic or postoperative hypotension, their use seems particularly appropriate in patients who are normotensive but who suffer from occasional hypertensive paroxysms.…”
Section: Preoperative Medical Treatmentmentioning
confidence: 99%